Independent regulatory authorities: contours of the debate and experience - Arora, Dolly (2018)
Taking note of the rapid growth of independent regulatory authorities and emerging evidence of significant variation in their design features as well as functional expression of independence across nations and within nations, sectors and levels of government, this article argues that regulatory discourses, including their institutional design and functionality, need to be understood in their specific political economy context and in the framework of larger goals of social justice and sustainable development, taking care of accountability, equity and environmental concerns that invite urgent attention. This would require a reopening of the debate on the parameters for evaluation of regulatory goals and design issues in the public domain involving all stakeholders. Rather than debating the extent of independence accomplished, one needs to consider the framework of regulation and the mechanisms which can address the challenge of competing rights claims in unequal power contexts. - Reproduced.
Keywords: Public administration; Governance